The Impact of Mangrove Ecosystems on Water Quality in Vaname Shrimp Farming - Brilian Amanat Taqwa; Arif Luqman; Awik Puji Dyah Nurhayati (PT FORMOSA CENDEKIA GLOBAL, 2026)
Mangrove ecosystems play a crucial role in maintaining coastal environmental stability while supporting sustainable aquaculture practices through biofiltration and carbon sequestration. However, empirical studies assessing the contribution of mangroves to water quality dynamics and sediment microbiomes in aquaculture ponds remain limited. This study aims to analyze the differences in water quality parameters, nutrients, and microbiome communities between ponds with and without mangroves in the biosphere buffer zone. Data were collected from several pond blocks with measurements of key variables, including pH, salinity, ammonium (NH₄), nitrite (NO₂), nitrate (NO₃), phosphate (PO₄), total organic matter (TOM), alkalinity, Vibrio bacteria, total bacteria, and plankton. Analyses were conducted using normality tests, the Mann-Whitney U test for intergroup differences, and Spearman’s correlation to assess relationships among variables. The results showed significant differences in salinity, TOM, alkalinity, and total Vibrio between ponds with and without mangroves. Moreover, strong correlations were observed between nutrients (PO₄, NH₄) and the dynamics of bacteria and plankton, indicating a close link between water quality and pond ecosystem health. These findings highlight the contribution of mangroves in maintaining environmental stability in aquaculture systems while enhancing production efficiency. Therefore, mangrove conservation is a key strategy to promote sustainable aquaculture practices and climate change mitigation.